DNA evidence of bowhead whale exploitation by Greenlandic Paleo-Inuit 4,000 years ago - Frederik Valeur Seersholm (Nature Portfolio, 2016)
Our current understanding of the demographic history of Greenland relies on preserved fossils. Here, the authors sequence ancient DNA from four midden deposits and find a prominent role for caribou, walrus and whale species in Paleo-Inuit cultures not evident from the fossil record.